Effectiveness of antiretroviral therapy in individuals who for economic reasons were switched from a once-daily single-tablet regimen to a triple-tablet regimen - Engsig, Frederik N; Gerstoft, Jan; Helleberg, Marie; Nielsen, Lars N; Kronborg, Gitte; Mathiesen, Lars R; Obel, Niels (Journal of acquired immune deficiency syndromes (1999), 2014)
To assess the impact on virological outcomes of a switch from branded single-tablet regimen (STR) including tenofovir, efavirenz, and emtricitabine (STR-TEE) to generic triple-tablet regimen (TTR), including tenofovir, efavirenz, and lamivudine (TTR-TEL), which was implemented on April 1, 2011 to obtain economic savings. From the Capital Region of Denmark (covering two-thirds of the Danish HIV patients), we included combination antiretroviral therapy (cART)-naive patients who administered STR-TEE from April 1, 2010 to March 31, 2011 (n = 111) or TTR-TEL from April 1, 2011 to March 31, 2012 (n = 56) and cART-experienced HIV patients who were on STR-TEE from April 1, 2010 (n = 356) or were switched from STR-TEE to TTR-TEL after April 1, 2011 (n = 512). We estimated the fraction with detectable HIV-RNA, development of the 184V/I resistance mutations, and time to switch of cART. Approximately 96.2% of cART-experienced patients on STR-TEE were shifted to TTR-TEL after April 1, 2011. For the naive STR-TEE and TTR-TEL patients, the fractions with detectable HIV-RNA at week 48 were 7.0% and 8.3% and for the cART experienced 4.0% and 4.4%, respectively. The 184V/I resistance mutation was detected in 1 cART-experienced patient on TTR-TEL with virological failure. The risk of switch to a new cART regimen was slightly increased in the cART-experienced population (difference in 1-year risk: 1.5%; 95% confidence interval: -2.4% to 5.4%). In settings comparable with the Danish health care system, the estimated economic savings from a switch from STR-TEE to TTR-TEL can be realized with negligible short-term risk of adverse outcomes.